A stranger in a strange land: the utility and interpretation of heterologous expression - Kramer, Elena M. (Frontiers in Plant Science, 2015)
One of the major goals of the modern study of evodevo is to understand the evolution of gene function across a range of contexts, including sub/neofunctionalization, co-option of genetic modules, and the evolution of morphological novelty. To these ends, comparative studies of gene expression can be useful for constructing hypotheses, but cannot provide direct evidence of functional evolution. Unfortunately, determining endogenous gene function in non-model species is often not an option. Faced with this dilemma, a common approach is to use heterologous expression (HE) in genetically tractable model species as a proxy for functional analyses. Such experiments have important limitations, however, and require caution in the interpretation of their results. How do we dissociate biochemical function from its original genomic context? In the end, what does HE actually tell us? Here, I argue that HE only sheds light on specific types of biochemical conservation, but can be useful when experiments are carefully interpreted.